2022
DOI: 10.1101/2022.04.22.489083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Free Fatty Acid-Binding Pocket is a Conserved Hallmark in Pathogenic β-Coronavirus Spike Proteins from SARS-CoV to Omicron

Abstract: As COVID-19 persists, severe acquired respiratory syndrome coronavirus-2 (SARS-CoV-2) Variants of Concern (VOCs) emerge, accumulating spike (S) glycoprotein mutations. S receptor-binding domain (RBD) comprises a free fatty acid (FFA)-binding pocket. FFA-binding stabilizes a locked S conformation, interfering with virus infectivity. We provide evidence that the pocket is conserved in pathogenic β-coronaviruses (β-CoVs) infecting humans. SARS-CoV, MERS-CoV, SARS-CoV-2 and VOCs bind the essential FFA linoleic aci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…S10). Of note, during preparation of this manuscript, a preprint reported a subpopulation of purified insect cell expressed (presumably expressed in low-pH insect cell media) SARS-CoV-1 spike ectodomain adopted a locked-2 conformation with lipid bound in RBD (Toelzer et al, 2022). We speculate that unlike SARS-CoV-2 S, where Domain D-loops In summary, SARS-CoV-1 and SARS-CoV-2 spikes exhibit complex conformational dynamics among Sarbecovirus spikes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…S10). Of note, during preparation of this manuscript, a preprint reported a subpopulation of purified insect cell expressed (presumably expressed in low-pH insect cell media) SARS-CoV-1 spike ectodomain adopted a locked-2 conformation with lipid bound in RBD (Toelzer et al, 2022). We speculate that unlike SARS-CoV-2 S, where Domain D-loops In summary, SARS-CoV-1 and SARS-CoV-2 spikes exhibit complex conformational dynamics among Sarbecovirus spikes.…”
Section: Discussionmentioning
confidence: 82%
“…S10 ). Of note, during preparation of this manuscript, a preprint reported a subpopulation of purified insect cell expressed (presumably expressed in low-pH insect cell media) SARS-CoV-1 spike ectodomain adopted a locked-2 conformation with lipid bound in RBD (Toelzer et al , 2022). We speculate that unlike SARS-CoV-2 S, where Domain D-loops are disordered in closed and open conformations, breaking interactions involving the ordered Domain D-loops in closed and open conformations represents a barrier to revert closed/open spike to locked conformations for SARS-CoV-1 S. This difference reflects how changes in Domain D may affect dynamics of Sarbecovirus spikes.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of HKU1-hCoV spike RBD indicates that the entrance to the hydrophobic pocket is obstructed by a glutamate residue (Ou et al, 2017). Notably, mutation of the glutamate residue to an alanine at the pocket entrance restores LA binding (Toelzer et al, 2022). Cryo-EM structures of OC43-hCoV spike also showed a hydrophobic pocket within the B domain, but it appears to be spatially too restricted to allow LA binding (Tortorici et al, 2019;Bangaru et al, 2022).…”
Section: Evolutionary Conservation Of La Binding To the Hydrophobic P...mentioning
confidence: 98%
“…Sequence alignments of spike proteins of the other human betacoronaviruses SARS-CoV, MERS-CoV, HKU1-hCoV and OC43-hCoV indicated that the hydrophobic pocket in the RBD (named the B domain in HKU1-hCoV and OC43-hCoV) is conserved (Toelzer et al, 2020). Importantly, the pocket is also conserved in all SARS-CoV-2 variants of concern (VOCs) to date, including the current VOC Omicron (Toelzer et al, 2022). Using surface plasmon resonance, betacoronavirus spike RBD proteins were tested for LA binding.…”
Section: Evolutionary Conservation Of La Binding To the Hydrophobic P...mentioning
confidence: 99%
See 1 more Smart Citation